Enhancing Biomedical Research Through Strategic Funding: A Comprehensive Review - Raju Vaishya; Abhishek Vaish; Marius M. Scarlat (National Board of Examinations Journal of Medical Sciences)
Background and Aims: Biomedical research play a vital role in driving health innovations, but the intricate funding landscape presents significant hurdles for researchers. This review seeks to explore the significance of funding in biomedical research, the obstacles encountered in obtaining such funding, and the economic ramifications of these investments. Methods: A narrative review was performed through an extensive literature search in databases such as PubMed, Scopus, and Web of Science from December 1 to 10, 2024. The search targeted peerreviewed articles, government reports, and publications related to biomedical research funding, using keywords like "biomedical research funding," "grant application processes," and "diversity in research funding." Results: The findings underscore the essential role of funding in promoting research productivity and innovation. Major challenges identified include a complicated grant application process, insufficient financial support for underrepresented groups, and a lack of transparency in funding mechanisms. Additionally, while there are signs of positive returns from investing in biomedical research, thorough analyses of the economic impacts are still lacking. Conclusions: The review highlights the necessity for strategic reforms to improve collaboration and transparency in funding mechanisms. Tackling the identified challenges is crucial to strengthen biomedical research efforts and ensure a variety of perspectives in addressing the urgent health issues facing society. Improved funding strategies can lead to better research outcomes and advancements in public health.